End‐member identification and spectral mixture analysis of CRISM hyperspectral data: A case study on southwest Melas Chasma, Mars. Issue 10 (9th October 2016) - Liu, Yang; Glotch, Timothy D.; Scudder, Noel A.; Kraner, Meredith L.; Condus, Thomas; Arvidson, Raymond E.; Guinness, Edward A.; Wolff, Michael J.; Smith, Michael D.
Abstract: We present spectral unmixing results over the southwest Melas Chasma region, where a variety of hydrated minerals were identified. We use the Discrete Ordinate Radiative Transfer radiative transfer model to simultaneously model Mars atmospheric gases, aerosols, and surface scattering and retrieve the single‐scattering albedos (SSAs) modeled by the Hapke bidirectional scattering function from Compact Reconnaissance Imaging Spectrometer for Mars (CRISM) data. We employ a spectral unmixing algorithm to quantitatively analyze the mineral abundances by modeling the atmospherically corrected CRISM SSAs using a nonnegative least squares linear deconvolution algorithm. To build the spectral library used for spectral unmixing, we use the factor analysis and target transformation technique to recover spectral end‐members within the CRISM scenes. We investigate several distinct geologic units, including an interbedded polyhydrated and monohydrated sulfate unit (interbedded unit 1) and an interbedded phyllosilicate‐sulfate unit (interbedded unit 2). Our spectral unmixing results indicate that polyhydrated sulfates in the interbedded unit 1 have a much lower abundance (~10%) than that of the surrounding unit (~20%) and thus may have been partially dehydrated into kieserite to form the interbedded strata, supporting a two‐staged precipitation‐dehydration formation hypothesis. In the interbedded unit 2 phyllosilicates have an abundance of ~40% and are interbedded with ~20% sulfates. The results, in combination with thermodynamic calculations performed previously, suggest that the interbedded phyllosilicates and sulfates likely formed through coupled basalt weathering and evaporation. The methodology developed in this study provides a powerful tool to derive the mineral abundances, aiming to better constrain the formation processes of minerals and past aqueous environment on Mars. Key Points: We developed a full spectral unmixing analysis method to quantitatively study mineral abundances on Mars Hydrated minerals including hydrated sulfates, jarosite, and phyllosilicates were identified and analyzed in southwest Melas Chasma, Mars The derived abundances provide constraint on the formation processes of hydrated minerals and past aqueous conditions on the study area